Management repercussions from the judicialization of medicines: an integrative review (Research, Society and Development, 2021)
Even with the implementation of the National Medicines Policy (PNM), access to medicines is still limited for a large part of the brazilian population, leading to judicialization as an alternative. As judicialized medicines are not foreseen in the annual health plans and the annual budget laws, this situation often results in unscheduled expenses. This study is an integrative review, with a quantitative characteristic, carried out from February to August 2020. Data collection was performed using the following databases: National Center for Biotechnology Information (PUBMED), Scientific Electronic Library Online (SCIELO), Literatura Latino-americana e do Caribe em Ciências da Saúde (LILACS) and trusted sites. It was observed that the judicialization of medicines has been progressively increasing across the country, requiring the manager to subsidize the process with the information he has at his disposal for a more appropriate decision. Also, other measures such as the insertion of a multiprofessional team assisting the judges in the judgment of lawsuits; greater awareness among prescribers about the importance of prescribing existing drugs in the Relação de Medicamentos Essenciais and a greater investment in Research and Development are some relevant points that can help to reduce and rationalize the judicialization of medicines.